2018
DOI: 10.1007/s10967-018-5953-7
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of uranium(III) in a molten chloride salt: a redox mechanistic study

Abstract: The most advanced methodology for the pyroprocessing of spent nuclear fuel is the electrorefining of uranium metal in LiCl–KCl eutectic, in which uranium is solubilized as U(III). The production of U(III) in LiCl–KCl eutectic by the chlorination of uranium metal using BiCl3 has been performed for research purposes. In this work, this reaction was studied in-situ by visual observation, electronic absorption spectroscopy and electrochemistry at 450 °C. The most likely mechanism has been determined to involve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…For use in reprocessing reactor fuel (pyroprocessing), electrochemistry is used for uranium dissolution. 6 In different melt mixtures, the required electrode potential for the oxidative dissolution of uranium metal changes and, in turn, so do the interactions with uranium cations and the melt constituent anions. In both chloride and fluoride molten salt melts, LiCl-KCl, FLiBe, FLiNaK, and LiCl-LiF, it is known that U(III) undergoes a one-step reduction to uranium metal (Eq.…”
Section: Electrochemistrymentioning
confidence: 99%
See 3 more Smart Citations
“…For use in reprocessing reactor fuel (pyroprocessing), electrochemistry is used for uranium dissolution. 6 In different melt mixtures, the required electrode potential for the oxidative dissolution of uranium metal changes and, in turn, so do the interactions with uranium cations and the melt constituent anions. In both chloride and fluoride molten salt melts, LiCl-KCl, FLiBe, FLiNaK, and LiCl-LiF, it is known that U(III) undergoes a one-step reduction to uranium metal (Eq.…”
Section: Electrochemistrymentioning
confidence: 99%
“…20,77 Lambert et al and Masset et al studied the reaction mechanism with BiCl 3 and had success. 6,46 Lambert et al found that adding BiCl 3 to U metal in a LiCl-KCl melt initiated the oxidative dissolution of U metal to U(III) in one hour. 6 A uranium oxidation study with BiCl 3 was performed at 450 °C in LiCl-KCl (see Fig.…”
Section: Electrochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Molten Salt technique is a simple and inexpensive technology to make new ceramic materials, (including one of them is PZT) by mixing stoichiometric oxides and followed by the sintering process at high temperatures in an atmosphere of salt solution. Sintering process is the main step of this technique, because some reaction mechanisms can occur from oxide components, including the diffusion process plays an important role, resulting in the formation of rather homogeneous compound 8) .…”
Section: Introductionmentioning
confidence: 99%